2022
DOI: 10.1101/2022.03.08.483554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introducing RELAX (the Reduction of Electroencephalographic Artifacts): A fully automated pre-processing pipeline for cleaning EEG data - Part 2: Application to Event-Related Potentials

Abstract: Electroencephalography (EEG) is commonly used to examine neural activity time-locked to the presentation of a stimulus, referred to as an Event-Related Potential (ERP). However, EEG is also influenced by non-neural artifacts, which can confound ERP comparisons. Artifact cleaning can reduce artifacts, but often requires time-consuming manual decisions. Most automated cleaning methods require frequencies <1Hz to be filtered out of the data, so are not recommended for ERPs (which often contain <1Hz frequenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…This means that the RELAX MWF_wICA method makes more data available for inclusion in analyses than most pipelines, reducing the risk that participant data needs to be excluded for having too few epochs for inclusion, or that results might be biased by exclusion of epochs containing neural activity due to inferior cleaning. Our companion article additionally indicated that MWF_wICA produced data that showed amongst the highest scores for reliability of ERPs across trials and participants, suggesting cleaning with MWF_wICA provided amongst the most consistency in detecting experimental effects (Bailey et al, 2022). The inclusion of more high-quality epochs for analysis and more reliable data has been suggested by simulations to improve study power even more than increasing sample size (Clayson, Carbine, et al, 2021; Kolossa & Kopp, 2018; Luck et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This means that the RELAX MWF_wICA method makes more data available for inclusion in analyses than most pipelines, reducing the risk that participant data needs to be excluded for having too few epochs for inclusion, or that results might be biased by exclusion of epochs containing neural activity due to inferior cleaning. Our companion article additionally indicated that MWF_wICA produced data that showed amongst the highest scores for reliability of ERPs across trials and participants, suggesting cleaning with MWF_wICA provided amongst the most consistency in detecting experimental effects (Bailey et al, 2022). The inclusion of more high-quality epochs for analysis and more reliable data has been suggested by simulations to improve study power even more than increasing sample size (Clayson, Carbine, et al, 2021; Kolossa & Kopp, 2018; Luck et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…Some default settings can be recommended. For example, the results reported in our companion paper indicated that the ICA methods infomax or fastICA with the symmetric setting were the best performers within RELAX (Bailey et al, 2022). If users can install cudaICA, this setting is likely to be optimal, providing both speed and the best performance (Raimondo et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous study used data pre-processing methods that we have since demonstrated to be less effective at cleaning artifacts compared to the method used in the current study (BLINDED FOR REVIEW). However, different EEG data cleaning approaches have been shown to produce only minor differences in study outcomes (Robbins et al, 2020), and these differences are still aligned in direction (Robbins et al, 2020, Bailey et al, 2022a, 2022b). As such, it seems unlikely that these explanations would produce such strong evidence for the null hypothesis if the results from our current study reflect the true result (we would expect more inconclusive results).…”
Section: Discussionmentioning
confidence: 99%
“…Each stimulus was presented for 250ms with an intertrial interval of 900ms (with a 50ms jitter). EEG data were pre-processed using the RELAX pipeline, which has demonstrated optimal cleaning of artifacts and preservation of ERP signals compared to other cleaning approaches (Bailey et al, 2022a(Bailey et al, , 2022b. This cleaning pipeline filtered the data from 0.25 to 80Hz with a notch filter from 47 to 53Hz, applied both Multiple Wiener Filters (MWF) and wavelet enhanced independent component analysis (wICA) to identify and remove muscle, eye movement and blink and drift artifacts from the data, and additionally the wICA reduced line noise, heartbeat and other artifacts.…”
Section: Statisticsmentioning
confidence: 99%